551 Outcomes of Sickle Cell Crisis in Relation to Pediatric Obstructive Sleep Apnea in the United States: A US Population cohort study. (3rd May 2021) - Patel, Palakkumar; Munoz, Tomas; Adavadkar, Pranshu
Abstract: Introduction: This study aimed to quantify the impact of obstructive sleep apnea (OSA) on the mortality, morbidity, and resources utilization among children admitted with Sickle cell crisis (SCC) Methods: This is a retrospective analysis using the 2016 and 2017 National Inpatient Sample Database. The Inclusion Criteria was a principal Diagnosis of SSC and age <18 years. OSA, as a Secondary Diagnosis, was identified using the appropriate ICD-10 CM codes. The Primary Outcomes were Inpatient Mortality, and secondary outcomes were: In-Hospital Length of Stay(LOS), Total hospitalization Cost, Blood transfusion (BT) requirement, and a requirement for Invasive mechanical ventilation (IMV). We used Multivariate Linear/ logistic regression to adjust for confounders including age and sex. Results: Out of 36, 484 children with SSC included in the study, 1450 children had OSA (SCC+OSA). SSC-OSA and SSC+OSA groups did not differ in gender, household income, and hospital characteristics, but did so in age (11.3 vs 12.4; p <0.001). OSA was most common in the age group of 13–18 (54%) and lowest in 0–4 (2.4%). Compared to SSC-OSA, the SCC+OSA cohort had significantly higher odds of mortality (adjusted OR= 11.9, [95% Confidence Interval: 1.02- 138.8], p=0.04). Additionally, SSC+OSA cohort was associated with increased odds of IMV (aOR=5.24 [CI: 1.84 – 14.8], p=0.002), longer LOS (adjusted mean difference (aMD)=0.67 [CI-0.32 – 1.02], p=<0.001), and higher hospitalization Cost (aMD=2818.76 [CI-1680- 4157], p=<0.001). No difference in BT (aOR=0.94 [CI: 0.68 – 1.29], p=0.71) was noted. Conclusion: This study demonstrates that the presence of OSA is associated with detrimental outcomes in SSC with higher in-hospital mortality, higher morbidity (Invasive mechanical ventilation rate), and higher resource utilization (LOS, total hospitalization cost). More attention to the screening, early diagnosis, and appropriate treatment of OSA is imperative to improve health outcomes in children with sickle cell disease. Support (if any):